Possible Relationships Between the Interannual Anomalies of the South-North Positions of the Northeastern China Cold Vortexes and the Sea Surface Temperatures (SSTs) During the Early Summer Periods - Fang, Yi-He; Lin, Yi-Tong; Ren, Hong-Li; Zhao, Chun-Yu; Zhou, Fang; Li, Qian; Gu, Chun-Lai (Frontiers in Earth Science, 2020)
The Northeastern China Cold Vortex (NCCV) processes during the early summer periods (June) from 1979 to 2018 were objectively identified in this study by using the daily precipitation data in Northeastern China (NEC), along with the six-hourly atmospheric circulation fields of ERA Interim/ECMWF, and the temperature field data and monthly mean sea surface temperature field data reconstructed by NOAA. Then, the NCCV processes from the objective identifications were divided into the Southern Cold Vortex (SCV) and the Northern Cold Vortex (NCV) according to the positions of their activity trajectories in the NEC geographical range. Next, an index was defined which could better represent the frequencies and intensities of the SCV and NCV. Relationships between the indices of the SCV and NCV and atmospheric circulation fields during the early summer months and the early SST fields were analyzed. Finally, the results of the sensitivity test of the AM2.1 model were used to verify the statistical analysis results. It was found that the SST factor impacting the intensity of the SCV was the North Atlantic Tripole (NAT) in early April. The anomalies of the NAT in April forced the formation of the “high-low pressure cooperation types” in early summer, which resulted in the intensity anomalies of the SCV. The SST factors impacting the intensity of the NCV were the south-north inverse SSTs of the Northwest Pacific (March) and the SSTs of the tropical Southeast Pacific (May). During the two examined periods of 1979 to 1999 and 2000 to 2018, the south-north inverse SST anomalies in the Northwest Pacific in March, as well as the SST anomalies in the tropical Southeast Pacific in May, were observed to have forced the formations of “double blocking low vortex types” and EAP teleconnection types during the early summer months, which resulted in anomalies in the NCV intensities. AM2.1 model was found to have good simulation effects regarding the observed impact results of the SSTs on the early circulation types during the early summer months, which further supported the conclusions achieved from the statistical analysis results.